2022
DOI: 10.3389/fmicb.2022.950587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary peNDF levels on digestibility and rumen fermentation, and microbial community in growing goats

Abstract: Physically effective neutral detergent fiber (peNDF) is a concept that accounts for the particle length of NDF in diets, sustaining the normal chewing behavior and rumen fermentation of ruminants. Specifically, peNDF>1.18 is the commonest one that is calculated from NDF and the percentage of feed dry matter left on the 1.18, 8.00, and 19.00 mm sieves. This study aimed to investigate the effects of different levels of peNDF>1.18 on the rumen microbiome and its correlation with nutrient digestibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…Four diets were formulated with similar ingredients, varying only in the proportions of two types of basal forage of differing chemical composition and particle size. Proper forage particle size is crucial for normal ruminal function and host health as it promotes a stable digesta mat, which increases the retention time of fiber particles, thereby promoting their fermentation by the rumen microbial community and stimulating reticulorumen motility, rumination, and salivation, neutralizing excessive acid production, and preventing a pH drop below levels required for optimal fermentation ( 28 , 29 ). Along with other factors, particle size also plays an important role in feed intake and, thus, in dietary nutrient and energy digestibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four diets were formulated with similar ingredients, varying only in the proportions of two types of basal forage of differing chemical composition and particle size. Proper forage particle size is crucial for normal ruminal function and host health as it promotes a stable digesta mat, which increases the retention time of fiber particles, thereby promoting their fermentation by the rumen microbial community and stimulating reticulorumen motility, rumination, and salivation, neutralizing excessive acid production, and preventing a pH drop below levels required for optimal fermentation ( 28 , 29 ). Along with other factors, particle size also plays an important role in feed intake and, thus, in dietary nutrient and energy digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Changing the acidogenicity value and the physically effective neutral detergent fiber contents of diets are complementary dietary formulation strategies for effectively manipulating the ruminal acid load ( 14 , 33 ), with the carbohydrate type (starch vs. fiber) greatly influencing the ruminal microbial population and the fermentation profile ( 29 , 34 , 35 ). In the present study, these changes were reflected in the alterations in the ruminal fluid fermentation profiles observed when corn silage was replaced with haylage and in the concomitant increase in the neutral detergent fiber-to-starch ratio (1.8 to 10.5).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that NAc supplementation did not alter the α-diversity indices (chao1, observed_otus, shannon, simpson, pielou_e), indicating bacterial diversity and richness in the rumen were not affected. The influence of the relative abundance of rumen bacteria is crucial to the apparent digestibility of nutrients and rumen fermentation characteristics, which may significantly affect ruminants’ productive performance and health status ( Ran et al, 2021 ; Zhou et al, 2022 ). Feeding NAc did not affect the α-diversity of the rumen bacterial community, which explains the unaltered rumen NH 3 -N and VFA molar percentages in the NAc treated group.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary variation has an important effect on rumen microbial community composition. Still, the ratio of forage to concentrate and the processing method of the diet are the main factors affecting rumen microbial population structure on the same diet basis ( Henderson et al, 2015 ; Bi et al, 2018 ; Zhou et al, 2022 ). More studies have shown that high grain diets can alter the structure of the rumen microbiota ( Mao et al, 2015 ; Seddik et al, 2019 ; Plaizier et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors observed that cattle fed a diet with cottonseed cake had lower rumination time and bite rate. According to Zhou et al [40], particles ≤ 1.18 mm may have lower digestibility because they have a higher rumen passage rate, mainly affecting fiber digestibility due to the low microbial action.…”
Section: In Vitro Digestibilitymentioning
confidence: 99%